Corporate sustainability as a strategy : Case study of Aquaplastic in Russia - Krynina, Vlada; Křečková Kroupová, Zuzana, 1972-; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This thesis studies the complexity and multidimensional character of the sustainability management of an enterprise using a case of a medium – sized regional producer of pipes in Russia. The author has researched the variety of theoretical works on sustainability in both world and Russian academic publishing and attempted to apply the key ideas on the case of manufacturing company.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses